2018
DOI: 10.1016/j.oooo.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled study to evaluate an experimental moisturizing mouthwash formulation in participants experiencing dry mouth symptoms

Abstract: The findings of a subjective questionnaire showed that an experimental moisturizing mouthwash provided greater relief than water only from dry mouth symptoms over 8 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 24 publications
1
18
0
1
Order By: Relevance
“…In Brunei, most patients have been indicated with an oral mouthwash that has been designed to stimulate salivary production. This was in line with the study conducted by Jose et.al, which concluded that moisturising mouthwash provided greater relief than water only from dry mouth symptoms [28]. However, it was found that 41 out of 73 patients use mouthwash, just over half of the sample size (Table 2).…”
Section: Discussionsupporting
confidence: 89%
“…In Brunei, most patients have been indicated with an oral mouthwash that has been designed to stimulate salivary production. This was in line with the study conducted by Jose et.al, which concluded that moisturising mouthwash provided greater relief than water only from dry mouth symptoms [28]. However, it was found that 41 out of 73 patients use mouthwash, just over half of the sample size (Table 2).…”
Section: Discussionsupporting
confidence: 89%
“…Water is widely accessible at low costs. Drinking water can temporarily relieve the subjective sensation of dry mouth [ 30 , 31 ]. However, the effectiveness and longevity of this strategy are limited [ 27 ], because the viscosity of water does not change with increasing shear [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although we extended the deadline to include more patients, new recruitment was difficult. Patients with such characteristics are not abundant and many of them are not well diagnosed or are under pharmacological treatments by their rheumatologist, as it was reported in other studies (Jose et al, ). In addition, many pSS patients have previously received many xerostomia treatments without success, and they do not want to start new trials.…”
Section: Discussionmentioning
confidence: 90%
“…For this reason, we found difficulties in comparing our results with previous studies. There are studies that did not find significant differences in improving xerostomia associated with pSS using other topical agents such as (Xialine) saliva substitute (Alpöz et al, ) and a mouthwash with cetylpyridinium chloride (Jose et al, ). Nonetheless, there are others that obtained positive results improving quality of life using a new natural formulation containing tea catechins (de Rossi et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation